2021
DOI: 10.3389/fmicb.2021.734526
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chicken Responses to Glycoconjugate Vaccination Against Campylobacter jejuni

Abstract: Campylobacter jejuni is a common cause of diarrheal disease worldwide. Human infection typically occurs through the ingestion of contaminated poultry products. We previously demonstrated that an attenuated Escherichia coli live vaccine strain expressing the C. jejuni N-glycan on its surface reduced the Campylobacter load in more than 50% of vaccinated leghorn and broiler birds to undetectable levels (responder birds), whereas the remainder of the animals was still colonized (non-responders). To understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 111 publications
0
27
0
Order By: Relevance
“…If we assume that in our experiment only low or very low concentrations of the supplemented acids reach the cecum, the indirect effects on Campylobacter load might be an interesting factor. While we did not include any analysis on the immune status of the chickens, in other studies, organic acids induced the formation of immunoglobulin Y ( IgY ) ( Park et al 2009 ), which was reported to induce inhibition of Campylobacter colonization ( Vandeputte et al 2019 ; Nothaft et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…If we assume that in our experiment only low or very low concentrations of the supplemented acids reach the cecum, the indirect effects on Campylobacter load might be an interesting factor. While we did not include any analysis on the immune status of the chickens, in other studies, organic acids induced the formation of immunoglobulin Y ( IgY ) ( Park et al 2009 ), which was reported to induce inhibition of Campylobacter colonization ( Vandeputte et al 2019 ; Nothaft et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… [ 219 ] Chicken Campylobacter jejuni /Vaccine Abundance of Clostridium spp., Ruminococcaceae and Lachnospiraceae was positively associated with vaccine-induced antigen-specific IgY responses. [ 220 ] …”
Section: Gut Microbiota Adaptation To Vitamin a Deficiency Impacts Ho...mentioning
confidence: 99%
“…Similarly, in Pakistani children, an abundance of Gram-negative bacteria such as Serratia and E. coli correlated positively with immune responses to HRV vaccine [ 233 ]. Other microbe abundances reported to be positively correlated with vaccine immunogenicity include Bifidobacterium longum vs. polio, Bacillus Calmette-Guérin and tetanus vaccines [ 215 ], Clostridiales vs. Salmonella Typhi /cholera vaccine [ 216 , 234 ] in humans; Collinsella / Lactobacillus LGG/ Bifidobacterium Bb12 vs. RV vaccine [ 61 , 235 , 236 ], Prevotella vs. influenza A vaccine [ 219 ] in pigs; Clostridium spp., Ruminococcaceae , Lachnospiraceae vs. Campylobacter jejuni [ 220 ] in chickens. Therefore, it is well established that perturbations of the gut microbiome by either antibiotics or dietary (VAD) can have major impacts on vaccine immunogenicity.…”
Section: Gut Microbiota Adaptation To Vitamin a Deficiency Impacts Ho...mentioning
confidence: 99%
“…Other key discoveries during this time were the observations that the C. jejuni oligosaccharyltransferase, PglB, attached sugars to a defined sequon (D/E-X 1 -N-X 2 -S/T where X 1 /X 2 cannot be proline) and that PglB would transfer any oligosaccharide (even derived from an unrelated LPS or CPS pathway) provided that the sugars were assembled on the same lipid used by the C. jejuni pathway i.e., undecaprenylphosphate (Und-P, also known as bactoprenyl) and the reducing-end sugar was an N-acetylhexosamine (Feldman et al, 2005;Kowarik et al, 2006). Due to the commonality of this N-glycan structure among all C. jejuni strains and the requirement for N-glycan expression for C. jejuni survival in chickens, we have been exploiting this heptasaccharide in the development of glycoconjugate poultry vaccines for the prevention of human foodborne illness (Nothaft et al, 2016;Nothaft et al, 2017;Nothaft et al, 2021b). For more reading on N-linked protein glycosylation in bacteria or bacterial glycoprotein biosynthesis, see (Nothaft and Szymanski, 2019) and (Nothaft and Szymanski, 2022), respectively.…”
Section: Frontiers In Molecular Biosciencesmentioning
confidence: 99%